Energy characteristics of plasma streams, generated by MPC - Astashynski, V.M.; Ananin, S.I.; Chebotarev, V.V.; Cherednychenko, T.N.; Ieliseiev, D.V.; Garkusha, I.E.; Kulik, N.V.; Ladygina, M.S.; Marchenko, A.K.; Morgal, Ia.I.; Petrov, Yu.V.; Solyakov, D.G.; et al. (Вопросы атомной науки и техники, 2013)
In present paper, results of experimental investigations of energy characteristics of plasma stream, generated by magnetoplasma compressor (MPC) are presented. It is shown that total energy contained in the plasma stream strongly depends on the discharge current, mass flow rate and sort of working gas. Radial distributions of energy density in plasma streams for different MPC modes of operations and energy transfer efficiency from the acceleration channel to the plasma stream are investigated. Представлены результаты экспериментальных исследований энергетических характеристик плазменных потоков, генерируемых магнитоплазменным компрессором (МПК). Показано, что полная энергия в плазменном потоке существенно зависит от разрядного тока, массового расхода и сорта рабочего газа. Также исследовано радиальное распределение плотности энергии в плазменном потоке и коэффициент передачи энергии от ускорительного канала в плазменный поток в разных режимах работы МПК. Представлено результати експериментальних досліджень енергетичних характеристик плазмових потоків, що генерує магнітоплазмовий компресор (МПК). Показано, що повна енергія в плазмовому потоці значним чином залежить від розрядного струму, масової витрати та сорту робочого газу. Також було досліджено радіальний розподіл густини енергії в плазмовому потоці і коефіцієнт передачі енергії від розрядного каналу в плазмовий потік в різних режимах роботи МПК.